Research and Design of High-Fidelity Experimental Bed System for Wireless Sensor Network - Heqing Huang; Wenjing Liu (Journal of Electrical and Computer Engineering)
Through in-depth analysis of the typical international wireless sensor network experimental system, the current design generally lacks the real-time diagnosis of the health state of the fault node and the experimental platform, the management and control mechanism to minimize the interference of the experimental task, and the highly integrated and friendly experimental entrance, which will have an obvious distortion impact on the experimental results. In view of the above shortcomings, on the basis of fully absorbing the design advantages in this research field, this paper studies and designs a high fidelity WSN experimental system, which covers the elements of open source, heterogeneity, analysis visualization, and experimental repeatability and innovates the mechanisms of real-time diagnosis, hierarchical parallel control, and TDMA to collect a large amount of experimental data. In order to support a variety of applications based on IEEE802.15.4 band, a high-fidelity and user-friendly experimental platform software and hardware system with 15 clusters and 130 heterogeneous nodes is studied and designed, which can simulate outdoor mesh networks with more than 6 hops. This paper is designed and implemented on Linux open-source platform. The whole system has low cost and can be replicated. The design results have good reference and application value for the research and design of wireless sensor network experimental system.